Belarusian Literature of the Last Thirty Years From the Perspective of Siarhiej Kavalou’s Book: Сяргей Кавалëў: Беларуская літаратура перыяду трансфармацыі. Абрысы замглëнага краявіду [Siarhiej Kavaloŭ: Belarusian literature of the transformation period: Outlines of a hazy landscape]. Lublin, Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, 2025, 270 p. ISBN: 978-83-227-9916-1 - Bakuła, Bogusław (Slavica, 2026)
This text is a review of a book by the renowned scholar of Belarusian literature Siarhiej Kavaloŭ, devoted to the history of Belarusian literature from 1985 to 2020. The author explores the dramatic fate of the literary generation known as the ‘Tutèjšyâ’ [Locals], who initiated a process of linguistic and artistic renewal after 1985. He traces the development of the literary scene following independence, highlighting key artistic events, and emerging figures in Belarusian literature. He also presents the political and social circumstances accompanying this process, right up to its stalling following the elections rigged by Lukashenko in 2020. Kavaloŭ writes about Belarusian poetry, prose, and drama. He analyses the work of the most important literary critics and literary historians. The book was published in 2025 at the Maria Curie-Skłodowska University in Lublin in Belarusian.